2016
DOI: 10.1111/aji.12547
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T‐cell activation attenuates hypertension,TNFα,IL‐17, and blood–brain barrier permeability in pregnant rats with angiogenic imbalance

Abstract: Problem Angiogenic imbalance during pregnancy is associated with immune activation, hypertension, increased T cell infiltration, and neurological insults. Method of Study On gestational day (GD) 12 timed-pregnant rats were infused with anti-angiogenic factors sFlt-1 and sEndoglin (4.7 and 7μg/kg) to create HELLP syndrome via mini-osmotic pumps for 8 days, with a subset of these rats having Orencia (2mg/kg) infused on GD13. On GD19, blood brain barrier (BBB) permeability was evaluated via Evan’s Blue infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 48 publications
3
32
1
Order By: Relevance
“…Accordingly, IL-17F appears as a target in Th17-mediated diseases such as RA [ 33 , 34 ]. That is interesting because although involved in RA, IL-17 also plays a key role in the pathogenesis of arterial hypertension, inducing the production of angiogenic factors and migration of endothelial cells [ 35 ]. IL-17A also mediates Angiotensin II (Ang II) induced renal injury and regulates renal sodium transporters, activating a serum and glucocorticoid regulated kinase 1 dependent pathway, and it could cause a sodium and water imbalance and therefore elevating the blood pressure [ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, IL-17F appears as a target in Th17-mediated diseases such as RA [ 33 , 34 ]. That is interesting because although involved in RA, IL-17 also plays a key role in the pathogenesis of arterial hypertension, inducing the production of angiogenic factors and migration of endothelial cells [ 35 ]. IL-17A also mediates Angiotensin II (Ang II) induced renal injury and regulates renal sodium transporters, activating a serum and glucocorticoid regulated kinase 1 dependent pathway, and it could cause a sodium and water imbalance and therefore elevating the blood pressure [ 35 - 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…On gestational day (GD) 12, mini-osmotic pumps (model 2002, Alzet Scientific Corporation, Cupertino, CA) were inserted into a subset of normal pregnant rats (NP) to allow infusion of sFlt-1 and sEng (4.7 and 7 μg/kg, respectively, R&D Systems, Minneapolis, MN) as previously described to induce the HELLP syndrome phenotype [ 15 , 16 , 20 ]. In the current study, we induced AKI by IR, since it has been reported to consistently induce AKI in experimental pregnant and non-pregnant animal models [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng) are anti-angiogenic proteins associated with preeclampsia and HELLP syndrome whose levels have been found to directly correlate with disease severity [ 13 , 14 ]. Furthermore, studies by our lab and others have reported that infusion or overexpression of sFlt-1 and sEng leads to the HELLP syndrome phenotype in pregnant rats [ 13 , 15 , 16 ]. Interestingly, sFlt-1 and sEng expression has been found to be increased in patients with chronic renal diseases and in experimental rodents following ischemia reperfusion (IR) [ 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental HELLP model obtained by chronic infusion of antiangiogenic factors, it was shown that the overall concentration of CD4+ and CD8+ T cells is increased, while Th17 and Treg concentrations were comparable between the groups (116,117). Later on, when these animals were treated with Abatacept, an antibody that blocks T cell activation, the biochemical parameters of HELLP syndrome were improved (118). However, the factor(s) leading to an increased T cell activation in HELLP, remains puzzling.…”
Section: T Cells In Hellpmentioning
confidence: 99%